Unraveling the genomic epidemiology and plasmid-mediated carbapenem resistance of Klebsiella pasteurii - Li, Xinyue; Song, Zexuan; Liu, Jinshuo; Jin, Jingguang; Wan, Hanxia; Chen, Huimin; Luo, Xinhua (Frontiers in Microbiology, 2025)
This study isolated a Klebsiella pasteurii strain, K1134, from the sputum of an ICU patient, revealing its resistance to the carbapenem antibiotics meropenem and imipenem. Whole-genome sequencing identified a plasmid pK1134-KPC, which carries the carbapenem resistance gene blaKPC-2. pK1134-KPC, belonging to the IncFIIpCP020359 plasmid group, exhibits a modular structure with blaKPC-2 embedded in a 32.09 kb accessory region containing multiple accessory genetic elements (AGEs). Comparative genomic analysis of 48 K. pasteurii isolates from 12 countries showed high genetic diversity, with strains clustered into three clades. Notably, K. pasteurii harbors extensive antimicrobial resistance genes across diverse AGEs, classifying it as multidrug-resistant. Twelve blaKPC-carrying AGEs were identified from the sequences of the isolates, classified into two groups: Tn7551 and Tn6296-related elements. The gene clusters for enterotoxins tilimycin and tilivalline, encompassing key regulators and operons, were present in nearly all strains, with incomplete clusters exclusively observed in clade 3 isolates. This study underscores the global dissemination and genetic adaptability of K. pasteurii, highlighting its potential role as a reservoir for resistance genes and emphasizing the need for robust surveillance to mitigate its public health impact.